2002
DOI: 10.1002/1521-3803(20020101)46:1<28::aid-food28>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Heat-resistance characteristics of ascospores of Eurotium chevalieri isolated from apricot juice

Abstract: A heat-resistant fungus was isolated from aseptically packaged apricot pulp. The fungus was identified as Eurotium chevalieri. Heat resistance of the fungus was studied at four different temperatures (70, 75, 80 and 83 degrees C) after activation of its ascospores for 30 min at 70 degrees C. D70, D75, D80 and D83 values of ascospores of Eurotium chevalieri were estimated by linear regression (log-survival vs. heating time) as 118.58, 34.15, 5.50 and 3.77 min, respectively. The z-value was determined in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In our study, we found that the D-values of A. chevalieri ranged from 69.85 to 0.44 min at heating temperatures ranging from 75 to 90 • C. Previously, during the thermal resistance study in apricot juice, D-values of 34.15 to 3.77 min were reported for A. chevalieri at temperatures ranging from 75 to 83 • C [5]. Indeed, the thermal resistance of ascospores from A. denticulatus, A. siamensis, and H. pallida has not been previously reported in the literature.…”
Section: Log-linear Modelmentioning
confidence: 40%
See 1 more Smart Citation
“…In our study, we found that the D-values of A. chevalieri ranged from 69.85 to 0.44 min at heating temperatures ranging from 75 to 90 • C. Previously, during the thermal resistance study in apricot juice, D-values of 34.15 to 3.77 min were reported for A. chevalieri at temperatures ranging from 75 to 83 • C [5]. Indeed, the thermal resistance of ascospores from A. denticulatus, A. siamensis, and H. pallida has not been previously reported in the literature.…”
Section: Log-linear Modelmentioning
confidence: 40%
“…These fungi are classified as those capable of surviving temperatures equal to or exceeding 75 • C for a duration of 30 min or more [2]. Heatresistant molds have been associated with spoilage incidents affecting various fruit juices and other fruit-based products, including fruit yogurt, ice cream with fruits, fruit juices [3], concentrated apple juice [4], apricot juice [5], and strawberry semi-finished product and sweetened beverages [6]. Additionally, some heat-resistant molds have the potential to produce mycotoxins, such as patulin, byssochlamic acid, verruculogen, and fumitremorgins [7].…”
Section: Introductionmentioning
confidence: 99%
“…The number of colonies is expected to increase until reaching the population of ascospores and to decrease after prolonged heating [ 50 ]. The high heat resistance of these species has been published elsewhere [ 13 , 51 , 52 ]. There has been no reported evidence of the spoilage of fruit products caused by other highly heat-resistant species: A. denticulatus , A. siamensis, and A. fennelliae .…”
Section: Resultsmentioning
confidence: 99%